Albania : Staff Report for the 1999 Article IV Consultation, Request for the Second Annual Arrangement Under the Enhanced Structural Adjustment Facility, and Request for Augmentation. (IMF Staff Country Reports; Country Report ;, 1999)
This paper reviews Albania's 1999 Article IV Consultation, Request for the Second Annual Arrangement Under the Enhanced Structural Adjustment Facility, and a Request for Augmentation. Inflation fell to 2 percent in March 1999. The return to growth and low inflation reflected the government's adherence to strong fiscal consolidation efforts. The domestically financed component of the deficit was reduced to 6.4 percent of GDP in 1998 from 10.8 percent of GDP in 1997. The external current account deficit also fell sharply from 12 percent of GDP in 1997 to 6 percent of GDP.